Improvement Hydroponic Cultivation Skills through The Demonstration Method in Student with Intellectual Disabilities - R. Rianatara; Erna Narsih Nagai (JASSI ANAKKU, 2021)
The purpose of this study was to determine the improvement of hydroponic plant cultivation skills in students with mild special needs in Schools with special needs-C Education Foundation for Special Needs Asih Manunggal Asih Manunggal Bandung through demonstration method. The type of research used isClassroom Action Researchwith 3 students with mild special needs as the subject. Data analysis techniques were carried out quantitatively and descriptively qualitatively. The results showed that there was a change in student scores with a significant increase in ability in hydroponic cultivation skills from each cycle of actions in learning that met the minimum completeness criteria, namely a score of 70 in skills lessons after students received hydroponic plant cultivation learning through the demonstration method. This success is because the demonstration method is very effectively used in learning hydroponic skills, where students can understand the real or imitation in a process or the workings of an object related to the lesson material. The demonstration method can be considered by teachers to be used in the skills learning process, especially hydroponic plant cultivation skills for mentally retarded students and can be developed for learning other materials.